Brolucizumab efficacy and safety single-arm descriptive trial in patients with persistent diabetic macular edema (BEST study): protocol for a single-centre, open-label, single-arm clinical trial in China - Huang, Ziyi; Hu, Yunyan; Shen, Chenxiao; Li, Jing; Liang, Anyi; Fang, Ying; Zeng, Jiahui; Liao, Huiyi; Zheng, Chunwen; Ouyang, Shuyi; Hu, Yijun; Cao, Dan; et al. (BMJ open, 2025)
IntroductionPersistent diabetic macular edema (DME) with inadequate responsiveness to conventional inhibitors of vascular endothelial growth factor (VEGF) has caused significant vision loss and substantial treatment burdens. Brolucizumab is a new-generation anti-VEGF agent with better anatomical efficacy and prolonged duration of action. This single-centre, open-label, single-arm design clinical trial aims to evaluate the efficacy and safety of intravitreal brolucizumab 6 mg in Chinese subjects with persistent DME.Methods and analysisA total of 52 adult subjects with persistent DME will be recruited from Guangdong Provincial People’s Hospital. All study eyes will receive three consecutive 6 mg brolucizumab injections at intervals of 6 weeks. Disease activity assessment (DAA) will be arranged at week 18, and if disease activity is detected, subjects will continue with dosing of brolucizumab every 6 weeks (at weeks 18 and 24). Otherwise, the dosing will be adjusted to every 12 weeks (at week 24). The primary endpoints will be the proportion of patients with central subfield thickness (CST) <300 µm and the proportion of patients with ≥5 letters visual improvement at week 28. The secondary endpoints will involve anatomical changes assessed through multimodal imaging techniques containing optical coherence tomography (OCT), OCT angiography (OCTA), ultrawide-field fundus photograph (UWFP), ultrawide-field fluorescein angiography (UWFFA), as well as safety assessment. Additionally, aqueous samples will be collected and cytokine levels will be assessed for exploratory analysis.Ethics and disseminationThis study has been approved by the Ethics Review Committee of Guangdong Provincial People’s Hospital (KY2024-319). This study will be conducted in accordance with the ethical principles that have their origin in the Declaration of Helsinki and that are consistent with the ICH E6 guidelines for Good Clinical Practice and the applicable regulatory requirements. The study results will be submitted to a peer-reviewed journal and presented at both local and international congresses.Trial registration numberNCT06498050.